Developing and evaluating the success of a family activated medical emergency team: a quality improvement report. Issue 3 (16th December 2014) - Brady, Patrick W; Zix, Julie; Brilli, Richard; Wheeler, Derek S; Griffith, Kristie; Giaccone, Mary Jo; Dressman, Kathy; Kotagal, Uma; Muething, Stephen; Tegtmeyer, Ken
Abstract : Background: Family-activated medical emergency teams (MET) have the potential to improve the timely recognition of clinical deterioration and reduce preventable adverse events. Adoption of family-activated METs is hindered by concerns that the calls may substantially increase MET workload. We aimed to develop a reliable process for family activated METs and to evaluate its effect on MET call rate and subsequent transfer to the intensive care unit (ICU). Methods: The setting was our free-standing children's hospital. We partnered with families to develop and test an educational intervention for clinicians and families, an informational poster in each patient room and a redesigned process with hospital operators who handle MET calls. We tracked our primary outcome of count of family-activated MET calls on a statistical process control chart. Additionally, we determined the association between family-activated versus clinician-activated MET and transfer to the ICU. Finally, we compared the reason for MET activation between family calls and a 2:1 matched sample of clinician calls. Results: Over our 6-year study period, we had a total of 83 family-activated MET calls. Families made an average of 1.2 calls per month, which represented 2.9% of all MET calls. Children with family-activated METs were transferred to the ICU less commonly than those with clinician MET calls (24% vs 60%, p<0.001). Families, like clinicians, most commonly called MET for concerns of clinical deterioration. Families also identified lack of response from clinicians and a dismissive interaction between team and family as reasons. Conclusions: Family MET activations were uncommon and not a burden on responders. These calls recognised clinical deterioration and communication failures. Family activated METs should be tested and implemented in hospitals that care for children.